Cancer stem cell and its niche in malignant progression of oral potentially malignant disorders. (December 2017) - Surendran, Subin; Siddappa, Gangotri; Mohan, Amrutha; Hicks, Wesley; Jayaprakash, Vijayvel; Mimikos, Christina; Mahri, Mohammed; Almarzouki, Fatima; Morrell, Kayla; Ravi, Ravindra; Govindan, Sindhu; Sushma, C.N.; et al.
Highlights: CD31, CD44, CXCR4 and SDF1 markers showed a progressive increase in expression levels with an increase in grade of dysplasia as compared to the normal cohort (p < 0.05). Co-expression of markers specifying CSCs (CD44), endothelial niche (CD31) and their cross talk (SDF-1, CXCR4) correlated with severity of dysplasia. CSCs in combination with its niche and their cross-talk may be used in identifying high-risk OPMD. Abstract: Objective: The purpose of this study was to determine association between cancer stem cells (CSCs) and their niche with progression of oral potentially malignant disorders. Materials and methods: Patients with histologically confirmed oral potentially malignant disorders, stratified into high/low risk lesions based on the degree of dysplasia and oral cancer were included in this study. Immunohistochemical profiling of markers of CSCs (CD44), endothelial cells (CD31) and CSC-vascular niche cross-talk (CXCR4 and SDF1) were carried out. Statistical analysis was performed to correlate the relationship of markers with histopathology grade (ANOVA, and χ 2 test, unpaired t test) using GraphPad InStat v3.06. Results: The study included 550 samples (349 patients) and analysis showed progressive increase in expression levels of CSC and its niche markers with increase in grade of dysplasia as compared to the normal cohort (p < 0.05). Co-expression analysis revealed that, in comparison to the normal cohort, a larger percentage of patients showed increased expression of CD31 and CD44 (CD31 high /CD44 high ; p < 0.05) and of CXCR4 and SDF1 (CXCR4 high /SDF1 high ; p = 0.04), suggesting an association of the CSCs and the vascular niche. Further, distribution of patients with CD44 high /CXCR4 high (p < 0.05) and CD31 high /SDF1 high (p = 0.01) was significantly increased in the high-risk group (18%), suggesting a correlation between CD44 + /CXCR4 + cells, the vascular niche and progression of oral dysplastic lesions. Conclusion: The increased expression of CSCs, the vascular niche and their cross talk markers are associated with increase in severity of dysplasia suggesting their role in the progression of oral potentially malignant disorders and may hence be used in identifying high-risk OPMD.